The immanent structure. Simultaneity of the whole and of the parts in Lévi-Strauss (Nóema, 2019)
Music, simultaneity and the relationship between the whole and the parts are three themes closely intertwined in Lévi-Strauss's work. To illustrate these themes, as gradually elaborated by Lévi-Strauss, we will follow a path in several stages along his intellectual journey: simultaneity, chess and music are the three figures that will guide us.
Keywords: Lévi-Strauss; structuralism; immanence; music; Spinoza; whole and parts; simultaneity